Pengaruh Promosi Terhadap Minat Beli Online Pada Marketplace Shopee : (Studi Kasus Pada Anggota AMGPM Ranting Wayame I) - Laura Nunumete; Dynne Andriany (P3M Politeknik Negeri Ambon, 2023)
Current developments in information technology have created new business opportunities. The current digital era has colored human life with various conveniences, one of which is the ease with which someone can interact and communicate without the limitations of space and time. The use of internet technology in the economic sector has made people's conventional/traditional shopping culture shift to an online shopping culture. . Currently, the e-commerce business is very popular and has a lot of interest, so companies are competing to create their own online or e-commerce stores to market their products. One of the methods used by producers in the marketing sector to increase product yields is through promotional activities. Promotion is a factor that is expected to increase buying interest. This research aims to determine tehe effect of promotion on buying interest in the shopee marketplace for members of AMGPM Ranting Wayame I. The amount of sample are 77 respondents using probability sampling technique by simple random sampling approach. This research using multiple linear regression analysis method with assist of SPSS 21 software, the regression equation Y= 13,004 + 0,481X. the hypothesis produce 4,842 of t-count with probability 0,000 or (p<0,05). Based on these results, it can be councluded that promotion have positive and significant effect on buying interest in the shopee marketplace for members of AMGPM Ranting Wayame I Keywords : Promotion, Buying Interest